Effectively managing human service organizations - Brody, Ralph (Sage sourcebooks for the human services series, 2005)
"Effectively managing human service organizations, third edition is a resource book for executive directors, middle managers, line supervisors, and graduate students who aspire to work in these roles. It provides both a conceptual framework and essential skills that managers need to make their organizations more effective. Easy to read, the book contains hundreds of real-life examples and specific guidance in developing skills necessary to manage large and small organizations." -- BOOK JACKET